2017
DOI: 10.1089/ten.tea.2017.0027
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Platelet-Derived Growth Factor-BB and Bone Morphogenetic Protein-2 Delivery from a Hybrid Calcium Phosphate/Alginate Scaffold

Abstract: Bone tissue engineering requires the upregulation of several regenerative stages, including a critical early phase of angiogenesis. Previous studies have suggested that a sequential delivery of platelet-derived growth factor (PDGF) to bone morphogenetic protein-2 (BMP-2) could promote angiogenic tubule formation when delivered to in vitro cocultures of human umbilical vein endothelial cells (HUVECs) and human mesenchymal stem cells (hMSCs). However, it was previously unclear that this PDGF to BMP-2 delivery sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 45 publications
0
23
0
1
Order By: Relevance
“…Published data support that formation of mature new vascular networks requires initiation by a pro-angiogenic growth factor such as VEGF followed by vessel stabilization by PDGF [63,64]. VEGF and PDGF have been extensively used to enhance neovascularization of implants to improve their engraftment and overall tissue regeneration [64,65]. It has been demonstrated that co-release of both VEGF [66] and PDGF [64] in vivo allows for not only formation of new blood vessels, but also ensures an overall higher degree of vessel maturity [63,67].…”
Section: Discussionmentioning
confidence: 98%
“…Published data support that formation of mature new vascular networks requires initiation by a pro-angiogenic growth factor such as VEGF followed by vessel stabilization by PDGF [63,64]. VEGF and PDGF have been extensively used to enhance neovascularization of implants to improve their engraftment and overall tissue regeneration [64,65]. It has been demonstrated that co-release of both VEGF [66] and PDGF [64] in vivo allows for not only formation of new blood vessels, but also ensures an overall higher degree of vessel maturity [63,67].…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Tengood et al showed that sequential delivery of bFGF followed by PDGF in a modified in vivo murine Matrigel plug assay with a hollow fiber delivery system produced better vascular integration versus non-sequential delivery of factors [52], the proposed mechanism of both being the initiation of endothelial sprouting with bFGF followed by vessel stabilization with PDGF at later time points. Interestingly, it is not just one specific sequence of factors, but many different combinations that have been tried that have shown promise with respect to enhanced vascularization [53][54][55].…”
Section: Changing Perspectives On Biomaterials Development For Promotmentioning
confidence: 99%
“…Many examples abound in the literature on the use of hydrogels for the encapsulation and controlled release of proteins for therapeutic applications. Among the possible proteins to be released from hydrogels, the delivery of growth factors has been widely reported as a strategy to improve wound healing [64,76,130,131,132,133,134,135,136,137,138,139,140,141], release of bone morphogenetic protein 2 (BMP-2) has been used for bone regeneration [142,143,144,145,146,147,148,149,150,151,152], encapsulation of insulin has been explored for oral delivery and/or triggered release under various conditions [153,154,155,156,157,158,159,160,161,162,163,164,165,166,167,168,169,170,171,172], encapsulation of different antigens in hydrogels has been explored in order to enhance the immune response for vaccine boosting effects and other immunotherapies [173,174,175,176,177,178,179,180], and encapsulation of antibodies has been use in localized delivery applications [181,182,183,184]. These are just a few of the many applications that have been explored involving the encapsulation of biomolecules, but they serve to exemplify why h...…”
Section: Proteins and Biomoleculesmentioning
confidence: 99%